MANAGEMENT ACCOUNT IN THE MANAGEMENT SYSTEM OF THE STATE MEDICAL ORGANIZATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The research is devoted to the issues of organizing and managing management accounts in state medical organizations. In the study, the need to introduce management accounting into the management system of the medical organization is justified. The introduction of management accounting is considered as one of the factors of increasing the efficiency of the management system of the state medical organization.